受攻击信息物理系统的分布式安全状态估计与控制 - 一种有限时间方法 = Distributed secure state estimation and control for CPSs under sensor attacks - a finite time approach - 敖伟 Ao Wei (2019)
研究具有非线性耦合特性信息物理系统 (Cyber physical systems, CPS) 在被攻击情况下的分布式有限时间状态安全估计和控制问题. 首先, 提出一种由分布式安全测量预选器和有限时间观测器组成的分布式有限时间状态安全估计策略, 可确保系统的状态在预设的有限时间之内被准确估计出来. 然后, 利用获得的安全状态估计, 借助反步设计方法, 建立一套分布式有限时间安全控制算法. 理论分析表明, 该方法可以保证系统能在有限时间内实现对给定信号的跟踪. 最后, 通过微电网系统仿真验证了所提方法的有效性. This paper investigates the problem of distributed secure state estimation and control for nonlinearly coupled interconnected cyber physical systems (CPS) under sensor attacks. Distributed schemes consisting of pre-selectors and observers are presented to solve the secure state estimation problem. Then, with the obtained state estimation and following the backstepping design procedure, distributed secure control algorithms are derived. Theoretical analysis shows that, with the proposed distributed secure observers and controllers, not only the state estimation of the CPS under attacks is obtained in a given finite time, but also the state tracking is ensured in a finite time. Finally, the developed algorithms are applied to an islanded micro-grid system as an illustration, verifying the effectiveness of the proposed method